Moribus Antiquis Res Stat Iudaea Virisque. Exempla in Flavius Josephus' Antiquitates Iudaicae - Göppinger, A. Judith (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2026, 2026)
Josephus’ Antiquities retell the entire Jewish history from the creation of the world to the outbreak of the Jewish War. But who makes this history? This study examines the literary construction of Moses, David, Judas Maccabee, and Agrippa I. through the lens of Roman exempla , showing that Josephus created these four Jewish protagonists in shape and form compatible with them, without turning the Jewish heroes into Romans. In this way Josephus proves not only the similarity of Jewish and Roman exemplary men, but he outdoes the Romans in their own categories of superiority, old age, and flawless virtuousness. Josephus’ Antiquitates erzählen die gesamte jüdische Geschichte von der Entstehung der Welt bis zum Ausbruch des Jüdischen Kriegs. Aber wer macht diese Geschichte aus? Die vorliegende Studie untersucht die literarische Charakterkonstruktion von Moses, David, Judas Makkabäus und Agrippa I. auf Basis römischer exempla und kann zeigen, dass Josephus die vier jüdischen Protagonisten römischen exempla gleichend konstruiert, ihnen aber ihr Judentum belässt. Damit beweist Josephus nicht nur die Vereinbarkeit von jüdischer und römischer Tradition, sondern kann die RömerInnen hinsichtlich Überlegenheit, langer Tradition und tadelloser Tugendhaftigkeit sogar in den Schatten stellen